Changes in social isolation and loneliness prevalence during the COVID-19 pandemic in Japan: The JACSIS 2020–2021 study - Murayama, Hiroshi; Suda, Takumi; Nakamoto, Isuzu; Shinozaki, Tomohiro; Tabuchi, Takahiro (Frontiers in Public Health, 2023)
Objective: The recent coronavirus disease 2019 (COVID-19) outbreak has changed people’s social connections with others and society. This study aimed to describe changes in the prevalence of social isolation and loneliness by demographic characteristics, socioeconomic status, health conditions, and outbreak situations in residential prefectures among Japanese people between the first year (2020) and the second year (2021) of the COVID-19 pandemic. Methods: We used data from the Japan COVID-19 and Society Internet Survey (JACSIS) study, a large-scale web-based nationwide survey conducted with 53,657 participants aged 15–79 years in August–September 2020 and September–October 2021 (25,482 and 28,175 participants, respectively). Social isolation was defined as less than once a week in the total frequency of contact with family members or relatives who were living apart and friends/neighbors. Loneliness was assessed using the three-item University of California, Los Angeles (UCLA) Loneliness Scale (score range, 3–12). We used generalized estimating equations to estimate the prevalence of social isolation and loneliness in each year and the difference in prevalence between 2020 and 2021. Results: The weighted proportion (95% confidence interval) of social isolation in the total sample was 27.4% (25.9, 28.9) in 2020 and 22.7% (21.9, 23.5) in 2021, representing a change of -4.7 percentage points (-6.3, -3.1). The weighted mean scores of the UCLA Loneliness Scale were 5.03 (4.86, 5.20) in 2020 and 5.86 (5.81, 5.91) in 2021, representing a change of 0.83 points (0.66, 1.00). The detailed trend changes for social isolation and loneliness were noted in the demographic subgroups of socioeconomic status, health conditions, and outbreak situation in the residential prefecture. Conclusion: Social isolation decreased from the first to the second year of the COVID-19 pandemic, whereas loneliness increased. Assessing the COVID-19 pandemic’s impact on social isolation and loneliness contributes to understanding who was particularly vulnerable during the pandemic.